A demanda de um centro de referência nacional para hanseníase no nordeste brasileiro : por que o excesso de pacientes? - Ferreira, Maria Lucy Landim Tavares (2009)
Until 2000, the Leprosy control in Brazil was a vertically integrated program. After this date, the program was considered a priority for primary care. However, the program remained centralized in some reference centers such as the D. Libânia National Reference Center for Sanitary Dermatology, located in Fortaleza, Ceará, Brazil (CDERM), responsible for 84% of the case detection in this municipality. The goal of this study was to investigate the factors associated with use of these services, and the potential for integration into primary health care. A cross-sectional survey was conducted with 600 users randomly selected in the outpatient clinic of the CDERM with the objective of determining the factors associated with demand for these services. Social, economic and demographic data, knowledge about the disease and perception about the services were collected. Eighty two percent of the participants had low social and economic status, 90% were referred from other health units; 87% had the multibacillary form. Sixty-nine per cent reported previous visits to other health units (HU). Fortynine per cent have never heard about leprosy, 24% reported fear of being discriminated against or suffering discrimination. Complementary medication was never missed for 57% treated in the CDERM and for 27% in other HUs. The commitment of the professionals was considered exemplary by 61% in the CDERM and by 14% in the other HUs. These facts reported by users, especially logistic ones and those related to the quality of the assistance and of the professionals might explain the concentration of users in this reference center.